Front Cover: The Quest for the Best Dual Orexin Receptor Antagonist (Daridorexant) for the Treatment of Insomnia Disorders (ChemMedChem 23/2020). (19th November 2020) - Boss, Christoph; Gatfield, John; Brotschi, Christine; Heidmann, Bibia; Sifferlen, Thierry; von Raumer, Markus; Schmidt, Gunther; Williams, Jodi T.; Treiber, Alexander; Roch, Catherine
Abstract : The Front Cover illustrates a circadian rhythm accompanied by daridorexant, Idorsia′s dual orexin receptor antagonist (DORA), investigated for the treatment of insomnia. It represents the quest for a DORA that would provide the next‐day benefits of a fully restorative night. The team at Idorsia set‐out to design a compound that antagonizes both orexin receptors, has a rapid onset of effect, and a duration of action sufficient for the night but short enough to avoid any negative residual activity the following morning, at optimally effective doses. The authors describe how these efforts resulted in daridorexant, a DORA which has recently successfully completed Phase 3 clinical studies. Good night insomnia! Artwork by Markenfels AG. More information can be found in the Full Paper by Christoph Boss et al.